The value of scientific information on climate change: a choice experiment on Rokua esker, Finland - Koundouri, Phoebe; Kougea, Eva; Stithou, Mavra; Ala-aho, Pertti; Eskelinen, Riku; Karjalainen, Timo P.; Klove, Bjorn; Pulido-Velazquez, Manuel; Reinikainen, Kalle; Rossi, Pekka Matias (Journal of Environmental Economics and Policy, 2012)
This article presents an application of the choice experiment method in order to provide estimates of economic values generated by water quantity improvements in the environment. More importantly, this is the first choice experiment study valuing scientific information and in particular scientific information on climate change. The case study of interest is Rokua in Northern Finland, a groundwater dependent ecosystem very sensitive to climate change and natural variability. The study deals with the uncertainty about the actual dynamics of the system and the effect of future climate change by exploring whether the public values sustained provision of resources for scientific research to better understand long-term environmental changes in Rokua. Data are analysed using a nested multinomial logit and an error component model. Evidence from this study suggests that individuals are willing to pay in order to assure scientific research so as to better understand long-term environmental changes. As a result, policy should consider investing in and supporting related research. Other aspects of water management policy valued by the public are water quantity, recreation, and total land income. We gratefully acknowledge the financial support from the European Union via the 7th Framework Program GENESIS: Groundwater and dependent ecosystems: New Scientific basis on climate change and land-use impact for the update of the EU Groundwater Directive; WP-6 Groundwater systems management: scenarios, risk assessment, cost-efficient measures and legal aspects. We finally thank two anonymous referees for constructive and insightful comments Koundouri, P.; Kougea, E.; Stithoua, M.; Ala-Ahob, P.; Eskelinenb, R.; Karjalainenc, T.; Klove, B. (2012). The Value of Scientific Information on Climate Change: A Choice Experiment on Rokua esker, Finland. Journal of Environmental Economics and Policy. 1(1):85-102. doi:10.1080/21606544.2011.647450 Senia 85 102 1 1